Breeding of wine yeasts with improved brandy aroma - Steger, Caroline,(Caroline Lucie Charlotte)1975- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.